(untitled) (Journal of Applied Learning and Teaching, 2022)
A large body of literature focuses on teachers’ service delivery and other related concepts. However, most of them have been judged to be generic. Measuring teachers’ service delivery generally does not picture events in specific areas. This study used a bootstrapped structural equation modelling to analyse how teachers’ use of library research materials (ULRMs) predicts teachers’ discharge of pedagogic duties across seven areas. A structured questionnaire collected primary data from 2,406 teachers and 7,218 students who consented and participated voluntarily. Exploratory and confirmatory factor analyses were used for dimensionality and goodness of fit tests. Convergent and discriminant validities were achieved based on average variance extracted (AVE) and squared correlation. The internal consistency measures were Cronbach’s alpha, McDonald’s Omega, and composite reliability. Results of the study showed among others that the teachers’ ULRMs is a significant direct predictor of teachers’ lesson preparation (β = .48, p < .001), use of instructional materials (β = .53, p < .001) and instructional delivery (β = .20, p < .001). Teachers’ lesson preparation had a significant direct effect on their use of instructional materials (β = .39, p < .001), classroom management (β = .19, p < .001), instructional delivery (β = .45, p < .001) and lesson evaluation (β = .29, p < .001). Significant mediation effects were recorded on the link between the ULRMs and teachers’ pedagogic duties. This study has empirically proven that teachers’ use of library research materials is crucial for the instructional process. It serves as the information bank in schools and as a source of instructional materials to enabling educational practitioners to plan and deliver practical lessons. Highlights: • Teachers’ discharge of pedagogic duties is an anchor point in secondary education. • Being able to evaluate lessons is associated with being able to provide feedback. • Teachers effectively utilised instructional materials, having planned how to use them. • Teachers’ lesson preparedness effectively decided their choice of instructional strategy.